The circular economy in corporate reporting: Text mining of energy companies’ management reports - Santos, M. R. C.; Rolo, A.; Matos, D.; Carvalho, L. (Energies, 2023)
This paper explores the implementation of the circular economy in the energy sector. The research findings contribute to our understanding of the practical application of the circular economy, enabling policymakers and stakeholders to make informed decisions and develop targeted strategies. The study analyzes 88 Portuguese companies’ reports, examining the presence of circular economy strategies and initiatives. The results reveal that energy sector companies tend to prioritize reporting their greenhouse gas reduction efforts over their circular economy strategies. The findings align with previous studies in the oil and gas industry, emphasizing the significance of sustainability reporting and potential biases in reporting practices. The study also identifies a gap between circular economy terminology and its representation in reports, indicating the need for greater incorporation of circular economy-oriented initiatives in the energy sector. The research highlights the role of technology in fostering innovation and calls for strategic alliances and knowledge sharing to drive circular economy practices. Further research is recommended to understand the barriers to implementing circular economy practices and identify effective solutions. Overall, this paper provides valuable insights for advancing the circular economy in the energy sector and achieving broader sustainability goals.